Identidade quilombola: diálogos entre educação ambiental e cultura em uma escola do campo em Campo Grande (MS) - Leão, Heide Cristiane Santos (2022)
With this work, we sought to analyze the reality of education aimed at children and young people from the Rural Black Community Quilombola Chácara Buriti, attended by the José do Patrocínio Municipal School, located in the rural space of Campo Grande (MS). It is believed that, in addition to scientific knowledge, the cultural roots of a people must be widely disseminated at all levels of education, especially when the school unit serves a portion of subjects from quilombola communities. Therefore, the objective was to propose a restructuring of the School's Political Pedagogical Project (PPP) in order to encompass the ethnic-racial issue, in interface with elements of Environmental Education, aiming at strengthening the identity and cultural valorization of students from the Quilombola Community in question. Methodologically, the work was anchored in qualitative research, supported by the techniques of bibliographic and documentary surveys. Data from the Municipal Department of Education (SEMED) were analyzed, collected in the References and Curriculum of the Municipal Education Network in Campo Grande (MS), as well as in the Pedagogical Political Project (PPP) of the school unit researched. In accordance with current legislation, adjustments were suggested for the school and the respective Pedagogical Political Project, aiming at the demand of that population. Teaching methodologies and actions to strengthen and recognize cultural identity were also proposed, anchored in Environmental Education, such as, for example, the implementation and maintenance of a school garden with the participation of relatives of students who live in the Rural Black Community Quilombola Chácara Buriti.